ANALISIS FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS DAN PENDAPATAN PEKERJA INDUSTRI BATOK KELAPA DI DESA TAMPAKSIRING GIANYAR - Suzuki, Koming Syun Mastra Junior; Purbadharmaja, Ida Bagus Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 4 (2022): Vol. 11 No. 4, April 2022 [1215-1619], 2022)
The handicraft industry has an important role in Bali Province as a supporter of the economy. Limited wood raw materials cause craftsmen in Tampaksiring Village to use coconut shells as works of art. The purpose of this study was to determine: 1) the direct influence of work experience, capital and technology on the productivity of coconut shell industrial workers in the village of Tampaksiring, Gianyar. 2) the direct influence of work experience, capital and technology on the income of coconut shell industry workers in Tampaksiring, Gianyar. 3) productivity mediates work experience, capital and technology on the income of coconut shell industry workers in Tampaksiring, Gianyar. Samples taken were all craftsmen in Tampaksiring, Gianyar. The analysis technique used path analysis. Based on the results of the analysis, it was concluded that work experience, capital and technology had positive significant influence on the productivity of coconut shell workers in Tampaksiring, Gianyar. Work experience, capital and technology have positive significant impact on the income of coconut shell workers in Tampaksiring, Gianyar. Productivity mediates work experience, capital and technology on the income of coconut shell workers in Tampaksiring, Gianyar. Keywords: Work Experience, Capital, Technology, Productivity, Income